Social Protest in Batavia: The Resistance of Entong Gendut in Early 20th-Century - Mubarok, Muhammad Zacky; Nurhasan; Wahyudi, Johan (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article analyzes social protests in early 20th-century Batavia, focusing on the resistance of community leader Entong Gendut against the Dutch East Indies government. Employing a historical approach, the research draws upon primary sources like newspapers, archival documents, and relevant historical literature, like in Memorie van Overgave Residen van Batavia 1987, De Locomotief newspaper. It reveals that Entong Gendut's resistance encompassed diverse forms of protest, including demonstrations, strikes, and public campaigns. His struggle against the colonial government heightened awareness of indigenous rights and ignited a broader social protest movement in Batavia. This research enriches our understanding of early 20th-century Batavian social protest dynamics and Entong Gendut's role in raising awareness of colonial injustice. The European government-imposed restrictions on the indigenous population to prevent them from expanding their political and social influence. It underscores the significance of historical studies in recognizing the contribution of local figures to anti-colonial struggles and their relevance to broader Indonesian history. They fought to defend their land from colonial rule.